USING INSTAGRAM ON ARABIC LEARNING IN THE POST-PANDEMIC ERA: STUDENTS’ VOICES - Ahmad Habibi Syahid; Mehrunnisa Ani Mufti (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2021)
The aim of this study was to investigate whether the use of Instagram on Arabic learning in the post-pandemic era can be one of the solutions for communicative online teaching and learning. Previous studies showed that the student found difficulties because of the lack of adequate facilities and infrastructures to use online platforms. However, the other student could use and operate it easily. This article discusses students’ perspectives on learning using Instagram, especially in improving Arabic language skills. The most supportive facility and infrastructure in conducting online learning is the presence of technology. In online learning, the learning management system that has already been widely used in online distance learning. However, today, social media such as Instagram can be used as a learning tool. The result of this study showed that Instagram was one of the solutions for communicative online teaching and learning in the pandemic and post-pandemic era according to the student perspective. Using descriptive analysis in describing the findings, the qualitative was chosen as the method in this study.